2014
DOI: 10.1177/0960327114533808
|View full text |Cite
|
Sign up to set email alerts
|

The relation between oxidative stress, inflammation, and neopterin in the paraquat-induced lung toxicity

Abstract: Paraquat (PQ) is a well-known quaternary nitrogen herbicide. The major target organ in PQ poisoning is the lung. Reactive oxygen species (ROS) and inflammation play a crucial role in the development of PQ-induced pulmonary injury. Neopterin is synthesized in macrophage by interferon γ and other cytokines. We aimed to evaluate the utility of neopterin as a diagnostic marker in PQ-induced lung toxicity. Sprague Dawley rats were randomly divided into two groups (sham and PQ), administered intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…Irreversible pulmonary fibrosis leading to respiratory failure is still the main cause of PQ poisoning-induced death [23]. Oxidative stress, endoplasmic reticulum stress, inflammation and alveolar epithelial cell apoptosis are possible mechanisms of PQinduced pulmonary fibrosis [24][25][26][27]. Recent years, many studies have confirmed the role of EMT in the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Irreversible pulmonary fibrosis leading to respiratory failure is still the main cause of PQ poisoning-induced death [23]. Oxidative stress, endoplasmic reticulum stress, inflammation and alveolar epithelial cell apoptosis are possible mechanisms of PQinduced pulmonary fibrosis [24][25][26][27]. Recent years, many studies have confirmed the role of EMT in the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The major toxicity mechanism of PQ poisoning is production of ROS [6,31] and use of antioxidants is therefore applicable. Tan et al [32,33] demonstrated that Mel presented a potent antioxidant effect due to its ability to scavenge ROS, with better properties than vitamins C and E. This superior antioxidant capacity is attributed to the cascade reaction in which Mel participates when scavenging free radicals, involving formation of Mel metabolites that also act as radical scavengers [34].…”
Section: Discussionmentioning
confidence: 99%
“…b-actin was used as loading control cells in the lungs. Considering the fact that oxidative stress is known to play an important role in the pathogenesis of number of human inflammatory disorders including those inflicting lungs [71,72], and PARP being reported to be key mediator in such a process [73][74][75], we analyzed the levels of MDA and GSH in the lungs as markers of oxidative stress. Indeed LPS treatment in mice was found to alter redox balance as MDA level was found to be increased and conversely GSH was found to be decreased upon LPS treatment.…”
Section: Discussionmentioning
confidence: 99%